THE ROLE OF SOCIAL MEDIA MARKETING, PRODUCT INNOVATION AND MARKET ORIENTATION ON MARKETING PERFORMANCE : AN EMPIRICAL STUDY ON SMEs in BANTEN - Kartika, Hayu (IJOSMAS, 2021)
The purpose of this study is to analyze the influence of social media marketing, Product Innovation, market orientation on marketing performance. In this study using quantitative methods and data analysis techniques Structural Equation Modeling Equation Modeling using SmartPLS 3.0 software. The sample of respondents selection method used the snowball sampling method. Online questionnaires were sent to respondents as many as 410 SMEs in Banten Province, 390 returned questionnaires and 20 questionnaires did not return. The results of data analysis show that social media marketing has a significant effect on marketing performance, Product Innovation has a significant effect on marketing performance, market orientation has a significant effect on marketing performance.